Impacto das novas tecnologias de informação e comunicação na participação e consciência política da juventude urbana de São Paulo - França, Maria Adelina (2015)
The present study analysed the influence of new information and communication technologies ICT in the political participation and consciousness of the youth, using a psicosocial approach. The use of internet was used as a basis for investigating the other variables impacting in this process. The sample was of 1165 respondents from different social economic status - SES, in the metropolitan area of São, ages ranging from 13 to 30 years old, from public and private schools and non-governmental organizations (NGO). Two main hypothesis were analysed: H1 the direct and positive correlation of the generalized use of internet on the youth political participation and consciousness; and, H2 correlation of the specific use of the internet on the youth political participation and consciousness. The demographic variables analysed were: age, sex, race, SES; and the competencies: political and social interest, personal and political efficacy, trust in people and in institutions, feelings of belonging, empathy, values, and content of the internet. The final results have shown that: (H1) the generalized use of internet is not directly linked to the youth political participation and consciousness, and it is highly influenced by SES; whereas (H2) only the specific use of internet is directly connected to the political participation and consciousness of the youth